2014
DOI: 10.4161/23328940.2014.984556
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species scavenger N-acetyl cysteine reduces methamphetamine-induced hyperthermia without affecting motor activity in mice

Abstract: Hyperthermia is a potentially lethal side effect of Methamphetamine (Meth) abuse, which involves the participation of peripheral thermogenic sites such as the Brown Adipose Tissue (BAT). In a previous study we found that the anti-oxidant N-acetyl cysteine (NAC) can prevent the high increase in temperature in a mouse model of Meth-hyperthermia. Here, we have further explored the ability of NAC to modulate Meth-induced hyperthermia in correlation with changes in BAT. We found that NAC treatment in controls cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 72 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…The Meth-induced sensitization, on the other hand, had a very severe impact on gene expression with a strong focus on pathways within mitochondria and endoplasmic reticulum. The suppression of mitochondrial function by Meth has been extensively described in the brain and in tissues that are rich in these organelles [75][76][77][78]. Meth-associated stress to the endoplasmic reticulum has been associated with blood-brain barrier disruption [79], and loss of astrocytes by apoptosis [80].…”
Section: Discussionmentioning
confidence: 99%
“…The Meth-induced sensitization, on the other hand, had a very severe impact on gene expression with a strong focus on pathways within mitochondria and endoplasmic reticulum. The suppression of mitochondrial function by Meth has been extensively described in the brain and in tissues that are rich in these organelles [75][76][77][78]. Meth-associated stress to the endoplasmic reticulum has been associated with blood-brain barrier disruption [79], and loss of astrocytes by apoptosis [80].…”
Section: Discussionmentioning
confidence: 99%
“…NAC-mediated inhibition of cellular thiol oxidation blunts activation of UCP1-dependent thermogenesis upon cold exposure or following ␤3-adrenergic stimulus (18). Additionally, acute activation of thermogenesis by methamphetamine, which requires functional BAT (41) and UCP1 (42), is substantially inhibited by NAC (43).…”
Section: Modification Of Thiol Redox Statusmentioning
confidence: 99%
“…Naturally occurring components from Terminalia chebula, possess antioxidant activities and useful as a treatment for asthma. 32) Our previous published studies have shown that pre-treatment of CA isolated from T. chebula reduces UPM-induced alveolar epithelium inflammation and junctional molecules-related barrier integrity. 17) Therefore, in the current study, we extended our study to investigate whether CA attenuates the damage of alveolar EMT by UPM.…”
Section: Discussionmentioning
confidence: 93%